2010
DOI: 10.1155/2010/706984
|View full text |Cite
|
Sign up to set email alerts
|

Decreased IP-10 and Elevated TGFβ1 Levels are Associated with Viral Clearance Following Therapy in Patients with Hepatitis C Virus

Abstract: The role of pro-fibrogenic cytokines in the outcome of infections with hepatitis C virus (HCV) and the response to treatment with pegylated interferon-alpha (pegIFNα) and ribavirin remains unclear. To address this issue, we assessed hepatic fibrosis and plasma markers pertinent to T-cell mediated fibrogenesis and inflammation at the start of treatment. Levels of soluble (s)CD30, interleukin-13 receptor alpha 2 (IL-13Rα2), total and active transforming growth factor-beta 1 (TGFβ1), interleukin-18 (IL-18) and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
0
12
1
1
Order By: Relevance
“…Unfortunately, the lack of available samples did not allow us to study this new parameter. We also did not find any correlation between plasma TGF-b levels and recovery in coinfected patients, contrasting with a previous report based on a score combining TGF-b levels and other factors [21]. The lack of detection of IL-10-producing cells, contrasts with other studies of HCV mono-infection [11].…”
Section: Core/ns2-specific Tgf-β+ T Cells (%) Core/ns2-specific Tgf-βcontrasting
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the lack of available samples did not allow us to study this new parameter. We also did not find any correlation between plasma TGF-b levels and recovery in coinfected patients, contrasting with a previous report based on a score combining TGF-b levels and other factors [21]. The lack of detection of IL-10-producing cells, contrasts with other studies of HCV mono-infection [11].…”
Section: Core/ns2-specific Tgf-β+ T Cells (%) Core/ns2-specific Tgf-βcontrasting
confidence: 99%
“…While the TGF-b profibrogenic, antiinflammatory and immunosuppressive activities certainly play a key role in HCV pathogenesis, its role in the control of HCV is still controversial. Indeed, high serum TGF-b levels [20] and a TGF-b high-producer genotype have been associated with failure [21] or with sustained virologic response to anti-HCV treatment, respectively [22]. Furthermore, increasing levels of TGF-b in the liver of HCV-infected patients enhanced fibrosis progression [23].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, TGF-b is a cytokine with multiple functions that has been associated with the development of hepatic fibrosis [20,21]. However, the role of TGF-b on the outcome of treatment against HCV is unclear and data are scarce and contradictory [22][23][24][25][26][27]. In this regard, high TGF-b levels have been described to diminish response to dual therapy in this population [22].…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of TGF-b on the outcome of treatment against HCV is unclear and data are scarce and contradictory [22][23][24][25][26][27]. In this regard, high TGF-b levels have been described to diminish response to dual therapy in this population [22]. On the contrary, a study observed a direct relationship between TGF-b levels and response to Peg-IFN in HIV-infected patients with acute hepatitis C [23].…”
Section: Discussionmentioning
confidence: 99%
“…During permanent attempts to improve therapeutic strategies, beside the recent approval of two novel direct acting antiviral compounds [2], several predictors of treatment response have been identified [3] with recent studies including gamma-glutamyl-transferase (gGT) [4], cholesterol [5], early viral kinetics [6], interferon-γ-inducible-protein-10 (IP10) [7], ferritin [8] and the interleukin-28B ( IL28B ) polymorphism [9] as further important predictors of sustained viral response (SVR) as well. However, the pursuit of further surrogate factors able to optimize therapeutic regimes remains challenging.…”
Section: Introductionmentioning
confidence: 99%